Big data analytics for sustainable computing - Haldorai, Anandakumar, 1983-; Ramu, Arulmurugan, 1985- (Advances in data mining and database management (ADMDM) book series., 2020)
Big data consists of data sets that are too large and complex for traditional data processing and data management applications. Therefore, to obtain the valuable information within the data, one must use a variety of innovative analytical methods, such as web analytics, machine learning, and network analytics. As the study of big data becomes more popular, there is an urgent demand for studies on high-level computational intelligence and computing services for analyzing this significant area of information science. Big Data Analytics for Sustainable Computing is a collection of innovative rese.